1995
DOI: 10.1111/j.2042-3306.1995.tb04915.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and blood metabolic responses to intense exercise during acute hypoxia and hyperoxia

Abstract: Summary Three horses performed exercise on a treadmill under normoxic conditions (F1O2–0.21) and during exposure to acute hypoxia (F1O2–0.17) and hyperoxia (F1O2–0.35) achieved by addition of nitrogen and oxygen to inspired air by means by an open flow system. The gases were added after the horses had walked and trotted at 2 submaximal speeds (2 and 4 m/s for 7–15 min). Thereafter, the treadmill speed was increased in 3 steps to attain near maximal oxygen uptake within 5–8 min (8–10.5 m/s for normoxia and hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
(27 reference statements)
2
7
0
2
Order By: Relevance
“…This was shown by the increase in muscle lactate and by the decrease in glycogen, ATP and CP observed immediately postexercise, which is in agreement with earlier studies (Valberg et al 1989;Essén-Gustavsson et al 1995;Schuback et al 2000). However, it is probable that the majority of the energy supply came from aerobic metabolism during the first steps of the incremental exercise test and that anaerobic metabolism occurred at the end of the exercise protocol.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was shown by the increase in muscle lactate and by the decrease in glycogen, ATP and CP observed immediately postexercise, which is in agreement with earlier studies (Valberg et al 1989;Essén-Gustavsson et al 1995;Schuback et al 2000). However, it is probable that the majority of the energy supply came from aerobic metabolism during the first steps of the incremental exercise test and that anaerobic metabolism occurred at the end of the exercise protocol.…”
Section: Discussionsupporting
confidence: 90%
“…Glycogen is known to be an important substrate source for horses performing maximal exercise (Valberg et al 1989;Essén-Gustavsson et al 1995;Schuback et al 2000). There is, however, no information available about glycogenolysis of PG and MG in equine skeletal muscle during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly increased muscle and plasma lactate levels showed that the energy demand was higher than what can be provided aerobically after the intensive trot in phase three. These levels were, however, lower, and ATP and CP levels higher, than the levels usually seen in connection with maximal treadmill exercise or after racing (Essén-Gustavsson and Valberg, 1987;Sewell et al, 1992;Essén-Gustavsson et al, 1995). After a race, which is generally considered to be maximal exercise to fatigue, horses have plasma lactate concentrations of 30-40 mmol/l, ATP of 10-20 mmol/kg d.w. and muscle lactate concentrations of 50-120 mmol/kg d.w. (Essén-Gustavsson and Valberg, 1987;Sewell et al, 1992).…”
Section: Discussionmentioning
confidence: 93%
“…If the blood flow to the working muscles is reduced in order to maintain skin blood flow during exercise in hot conditions, the aerobic metabolism may be limited and the release of lactate and heat from the muscle may be decreased. When horses perform intense exercise, energy is released by a combination of both aerobic and anaerobic metabolism, as indicated by a high oxygen uptake, increased red cell volume, high concentrations of lactate in muscle and blood and low concentrations of adenosine triphosphate (ATP) and creatine phosphate (CP) (Persson, 1967;Harris et al, 1984;Snow et al, 1985;Essén-Gustavsson et al, 1995). The limited intramuscular ATP stores play an important role during maximal exercise, when the energy demand is higher than that which can be provided aerobically (through oxidative phos-phorylation) and anaerobically (by CP breakdown or through the glycolytic pathway).…”
Section: Introductionmentioning
confidence: 99%
“…61(1): [13][14][15][16][17][18][19][20] 1999 pattern of fibre recruitment, muscle fibre composition and contractil and metabolic properties of the muscular fibres [20,25,38]. Even the high velocity exercises performed by Thoroughbred racehorses have a marked dependence on aerobic metabolism, since a high oxygen uptake and an increased red cell volume have been reported [8,25,38]. However, an important glycolytic capacity is also required during maximal exercise bouts or sprints, as high levels of blood lactate, glycerol, ammonia, hypoxantine, uric acid and allantoin have been found after racing [28,29,34].…”
mentioning
confidence: 99%